Access to Essential Facilities under the Commerce Act in the Light of Experience in Australia, the European Union and the United States - Korah, Valentine (Victoria University of Wellington Law Review, 2000)
Drawing on recent developments in Australian, United Kingdom and United States jurisprudence, Professor Korah casts doubt on the approach recently taken by New Zealand courts in one of the most controversial areas of competition law: the access to its facilities that a corporation in a dominant position must give to its would-be competitors. She argues that before imposing such obligations courts ought to be more sophisticated in assessing the economic effects of such obligations and especially the need to preserve an incentive to make the considerable investment required to create such facilities. Professor Korah was the 1999 Chapman Tripp Fellow. This article is an edited version of a paper presented at the offices of Chapman Tripp during the tenure of the Fellowship.